2019
DOI: 10.3390/su11226374
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management and the Sustainable Development of Social Work

Abstract: The growing shortage of skilled social workers, accompanied by an ageing population and the increasing number of fragile, elderly individuals that require social services, poses a serious challenge for our society. The magnitude of this problem is seen in the various predictions hypothesizing that, globally, there is likely to be a shortfall of millions of social workers for the successful provision of social services. To make matters worse, there are not enough social work students to fill that void, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 98 publications
1
16
0
Order By: Relevance
“…However, that time can also be spent for professional purposes, thus having positive effects such as keeping the workers in touch with managers and customers, keeping employees up to date with information on the market and regarding the organizational environment, helping employees quickly access important information from public or specialized sources, using specialized software for doing their work. As our study has shown what information processes people access where they live and work, it contributes to possible future research on social sustainability [51]. We support this aspect, due to the fact that social sustainability promotes well-being at the workplace and information regarding the impact of technology on employees.…”
Section: Discussionsupporting
confidence: 69%
“…However, that time can also be spent for professional purposes, thus having positive effects such as keeping the workers in touch with managers and customers, keeping employees up to date with information on the market and regarding the organizational environment, helping employees quickly access important information from public or specialized sources, using specialized software for doing their work. As our study has shown what information processes people access where they live and work, it contributes to possible future research on social sustainability [51]. We support this aspect, due to the fact that social sustainability promotes well-being at the workplace and information regarding the impact of technology on employees.…”
Section: Discussionsupporting
confidence: 69%
“…Knowledge synthesis is a fundamental element of KM [31] and healthcare settings [14]. Results showed many ways of creating knowledge, such as interactions of colleagues [32], formal and informal meetings [33], and recorded evidence [34].…”
Section: Knowledge Synthesismentioning
confidence: 99%
“…Previous research suggests that knowledge management is a managerial activity involving developing, transferring, storing and implementing knowledge (Hicks et al, 2006). Utilising knowledge management practices offers organisations the potential to achieve competitive advantage and continuous improvement (Colnar et al, 2019;Lojpur et al, 2015) with the final aim of delivering the best possible organisational performance (Shih et al, 2018), which can be understood as the best possible quality of their services.…”
Section: Literature Reviewmentioning
confidence: 99%